Continuous-Flow Synthesis of Cyclobutenes Using LED Technology - Smyth, Megan; Moody, Thomas S.; Wharry, Scott; Baumann, Marcus (Synlett, 2023)
Cyclobutenes are highly strained ring systems of considerable synthetic interest that can be accessed via cycloaddition reactions between alkenes and alkynes. However, their traditional preparation relies on photochemical [2+2] cycloadditions that exploit low-wavelength UV radiation emitted from inefficient medium-pressure Hg lamps. This paper reports on the development of a modern approach using a high-power LED set-up emitting at the boundary of UV-A and visible light in conjunction with a continuous-flow reactor. The resulting flow process renders a series of cyclobutenes from maleimides and various commercial alkynes. This provides a more energy-efficient approach that is readily scalable to access multigram quantities of cyclobutenes in high chemical yields and short residence times. The value of these products is exemplified by flow-based hydrogenations yielding highly substituted cyclobutanes which represent sought after building blocks in modern medicinal chemistry programs.
Keywords: photochemistry; cycloaddition; cyclobutene; light-emitting diode (LED); flow chemistry